The Association between Knowledge, Family Support, and Blood Sugar Level in Type 2 Diabetes Mellitus Patients - Herawati, Ratna; Pamungkasari, Eti Poncorini; Sugiarto, Sugiarto (Indonesian Journal of Medicine, 2018)
Background: Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia. The incidence of DM has increased due to lack of knowledge about DM and changes in lifestyle. The purpose of this study was to analyze the relationship of knowledge about DM, family support, and blood sugar levels in type 2 DM patients in Jebres health center, Surakarta.Subjects and Method: A cross sectional study was conducted at Sibela and Ngoresan Surakarta health center. The study subjects were 100 DM patients selected by purposive sampling. Socio-economic data, knowledge and family support were measured by questionnaires. Blood sugar levels were measured using a spectrophotometer. The data were analyzed using a multiple logistic regression.Results: A total of 66 DM patients had a high level of knowledge, 58 patients received strong family support, and 76 people had normal blood sugar levels. High knowledge about DM (OR= 0.87; p= 0.001) and strong family support (OR= 0.99; p= 0.017) lowered blood sugar levels in DM patients.Conclusions: High knowledge about DM and strong family support reduce blood sugar levels in DM patients.Keywords: knowledge about DM, family support, blood sugar level, type 2 diabetes mellitusCorrespondence:Ratna Herawati. Masters Program in Family Medicine, Universitas Sebelas Maret. Jl. Ir Sutami 36A, Surakarta 57126, Central Java. Email: ratna_herawati_dokter@yahoo.co.id.Indonesian Journal of Medicine (2018), 3(1): 49-55https://doi.org/10.26911/theijmed.2018.03.01.07